2009
DOI: 10.17221/912-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Release of Strawberry Aroma Compounds by Different Starch-Aroma Systems

Abstract: Abstract:In the food industry, the addition of flavours is used to reinforce the aroma profile of different goods. However, interactions between starch and aroma compounds can occur, and this can impact upon aroma release and perception. In the present study, we have investigated the influence of starch type on aroma release from starch-aroma systems. The food model system used was composed of an aqueous starch dispersion (1 g dry starch/100 g dispersion) and 10 aroma compounds (ethyl butanoate, ethyl 2-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It is composed of glucopyranose units, and its main components are amylose (linear polymer) and amylopectin (short, branched chains), whose ratio affects the physical properties of a particular starch. Furthermore, starches can also serve as carriers for encapsulation of flavor compounds and thus contribute to flavor quality [42,43]. Starch interacts with flavor compounds, and these interactions depend on various factors such as polarity, molecular weight, hydrophobicity, volatility and solubility of flavor compounds, nature of the starch and competition among flavor compounds [43][44][45].…”
Section: Starch-flavor Compounds Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is composed of glucopyranose units, and its main components are amylose (linear polymer) and amylopectin (short, branched chains), whose ratio affects the physical properties of a particular starch. Furthermore, starches can also serve as carriers for encapsulation of flavor compounds and thus contribute to flavor quality [42,43]. Starch interacts with flavor compounds, and these interactions depend on various factors such as polarity, molecular weight, hydrophobicity, volatility and solubility of flavor compounds, nature of the starch and competition among flavor compounds [43][44][45].…”
Section: Starch-flavor Compounds Interactionsmentioning
confidence: 99%
“…Furthermore, starches can also serve as carriers for encapsulation of flavor compounds and thus contribute to flavor quality [42,43]. Starch interacts with flavor compounds, and these interactions depend on various factors such as polarity, molecular weight, hydrophobicity, volatility and solubility of flavor compounds, nature of the starch and competition among flavor compounds [43][44][45]. The formation of helical inclusion complexes was reported as an example of the specific binding of starch (especially the linear amylose) and flavor compounds in such a way that the flavor molecules are wrapped in a left-handed single helical structure [10,46].…”
Section: Starch-flavor Compounds Interactionsmentioning
confidence: 99%
“…It is worth mentioning that at ≈ 11% RH within 25-45 • C, films possess ≤ 4% moisture content (Chowdhury & Das, 2010;Chowdhury & Das, 2012). Regarding aroma loss through Starch-MC film, reports of Quezada Gallo et al (1999) on interaction of aroma compounds with methylcellulose in films deterring the quality of packaged food material and Vidrih et al (2009) on interaction of aroma with starch in dispersion, seem quite interesting. It may also be noted in the same figure that starch films are transparent and perhaps, such transparency downgrades the colour attributes of tastemaker powder whilst keeping tea unaffected.…”
Section: Quality Attribute Ranking Of Individual Tea and Tastemaker Smentioning
confidence: 99%
“…Hydrophilic biopolymers possess better aroma retention capacity (Das & Bal, 1999). In a model food system containing aqueous starch dispersion and commercial strawberry flavour, Vidrih, Zlatić, and Hribar (2009) reported that starch had significant influence on retention of aroma compounds. Studies on interactions between solutions of polysaccharides (modified corn and waxy corn starches) and model aroma compounds (limonene, isoamyl acetate, ethyl hexanoate and ß-ionone) using exponential dilution technique showed the aroma retention ability of the polysaccharides (Langourieux & Crouzet, 1995).…”
Section: Introductionmentioning
confidence: 99%